2020
DOI: 10.24272/j.issn.2095-8137.2020.068
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic diversity within three South American whip spider species (Arachnida, Amblypygi)

Abstract: Cryptic diversity (CD), the presence of highly divergent phylogenetic lineages within closed morphological species, has been documented for many taxa. Great arachnid orders such as Araneae or Scorpiones are well studied and many cases of CD have been described therein; to date, however, related research on smaller arachnid orders, such as whip spiders (Amblypygi), remains lacking. In the current study, we investigated CD based on cytochrome oxidase 1 ( COI ) in three nominal species of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Eight morphologically and genetically delimited species of the tarantula genus Brachypelma Simon, 1891 occur across the distribution of Acanthophrynus (Mendoza & Francke, 2020). Recent genetic studies on phrynid whip spiders of the genera Heterophrynus and Phrynus suggested large pairwise genetic distances may reflect previously unrecognized cryptic diversity (Esposito et al, 2015; Reveillion et al, 2020). Pairwise genetic distances within Acanthophrynus resemble intra‐ and interspecific distances among morphologically diagnosable whip spider species of other genera, suggesting the monotypic Acanthophrynus is a complex of three or four cryptic species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight morphologically and genetically delimited species of the tarantula genus Brachypelma Simon, 1891 occur across the distribution of Acanthophrynus (Mendoza & Francke, 2020). Recent genetic studies on phrynid whip spiders of the genera Heterophrynus and Phrynus suggested large pairwise genetic distances may reflect previously unrecognized cryptic diversity (Esposito et al, 2015; Reveillion et al, 2020). Pairwise genetic distances within Acanthophrynus resemble intra‐ and interspecific distances among morphologically diagnosable whip spider species of other genera, suggesting the monotypic Acanthophrynus is a complex of three or four cryptic species.…”
Section: Discussionmentioning
confidence: 99%
“…Pairwise genetic distances in the 12S, 16S and COI loci of Acanthophrynus were compared to intra‐ and interspecific distances among morphologically distinct but closely related whip spider species of three genera, using data from GenBank: five species of Damon C.L. Koch, 1850 from Prendini et al (2005); three species of Heterophrynus Pocock, 1894 from Reveillion et al (2020); and four species of Paraphrynus Moreno, 1940 from Seiter et al (2020). Sequences were aligned with the Acanthophrynus sequences using online mafft version 7 (Katoh et al, 2019) with the iterative refinement method G‐INS‐I and a 200PAM/κ = 2 parameter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the first species, Phalangium reniforme , was described in 1758 by Carl von Linné, few species were described before the end of the 19th century. However, the interest in this group continues to grow, as the number of species described and the studies published on whip spider systematic and morphometry increase each year (Chapin & Hebets, 2016; Harvey, 2003; Maquart et al, 2018; McArthur et al, 2018; Miranda & Reboleira, 2019; Réveillion & Maquart, 2018; Reveillion et al, 2020; Weygoldt, 2000; Zhu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Whip spiders seem to display rather low diversity, though their fossil records date back to the Upper Carboniferous [1,4]. Recent studies, however, suggest that the amblypygid diversity might be considerably larger, but its cryptic nature hampers its thorough characterization by most of the current approaches [5][6][7]. Amblypygids are classified into two suborders, namely the Paleoamblypygi, represented by the monotypic genus Paracharon, and the Euamblypygi, which includes four families (Charinidae, Charontidae, Phrynidae, and Phrynichidae) encompassing about 220 extant species placed in 17 genera [3,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%